2017
DOI: 10.1002/osp4.111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of educational and lifestyle interventions to prevent paediatric obesity: systematic review and meta-analyses of randomized and non-randomized controlled trials

Abstract: SummaryObjectiveThis review and meta‐analysis aim at updating a previous meta‐analysis carried out by Waters et al. on the efficacy of interventions aimed at preventing childhood obesity and at identifying predictors of outcome.MethodsUsing an ad‐hoc search string, PubMed database was searched for studies assessing body mass index reduction associated with programmes lasting ≥12 weeks in overweight and obese children aged 2–18 years. Studies designed for children with eating disorders or relevant comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 88 publications
1
44
0
2
Order By: Relevance
“…The systematic reviews relating to pre-schoolers and healthy eating have been predominantly about preventing or managing obesity, with a focus on the effectiveness of interventions which change weight status [ 25 ]. Other systematic reviews have focused on specific determinants of obesity such as diet, physical activity and other obesogenic behaviours including sedentary behaviour and sleep [ 26 , 27 ] or type of intervention such as educational and lifestyle interventions [ 28 ], influence of the food environment [ 29 ] or nutrition policies at child-care centres and impact on role modelling [ 30 ]. The range of research questions in these reviews has been wide, as have been the recommendations for decision-makers, practitioners and policy-makers.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic reviews relating to pre-schoolers and healthy eating have been predominantly about preventing or managing obesity, with a focus on the effectiveness of interventions which change weight status [ 25 ]. Other systematic reviews have focused on specific determinants of obesity such as diet, physical activity and other obesogenic behaviours including sedentary behaviour and sleep [ 26 , 27 ] or type of intervention such as educational and lifestyle interventions [ 28 ], influence of the food environment [ 29 ] or nutrition policies at child-care centres and impact on role modelling [ 30 ]. The range of research questions in these reviews has been wide, as have been the recommendations for decision-makers, practitioners and policy-makers.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the longest was three years with one to two years being most common. [49] The trial utilised a cluster randomized design and electronic tablets for data collection saving time compared to paperbased surveys [55] . Local, high quality data was recognised by community partners as to a key aspect of the community engagement and ongoing intervention adaptation.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Therefore, the key to obesity prevention may be the home environment where parents shape the food, meal, and physical activity environment by being responsible for availability, timing, frequency of meals and activity, and through the way they interact with their children [ 21 ]. Indeed, several systematic reviews have concluded that interventions to prevent overweight and obesity in various settings obtain higher effects when parents are involved [ 22 27 ]. Research has identified different parenting practices and parent-child interactions which shape children’s health-related behaviours [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Healthy School Start programme builds on Social Cognitive Theory (SCT) with parental self-efficacy and observational learning as central constructs [ 34 ]. The programme is in line with the latest evidence regarding the prevention of childhood obesity namely that schools should be a focal point of obesity prevention efforts, interventions should involve multiple components and include the home environment [ 26 , 27 ]. The programme is complex and comprises several components such as health information to parents, motivational interviewing with parents and educational activities for the children followed by home assignments performed together with parents.…”
Section: Introductionmentioning
confidence: 99%